2022
DOI: 10.3390/antibiotics11050632
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Rates of Ventilator-Associated Pneumonia and COVID-19 Associated Pulmonary Aspergillosis in Critically Ill Patients with SARS-CoV2 Infection in the Second Wave: A Retrospective Chart Review

Abstract: Due to multiple risk factors, the rate of ventilator-associated pneumonia in critically ill COVID-19 patients has been reported in a range of 7.6% to 86%. The rate of invasive pulmonary aspergillosis in this cohort has been reported at 4% to 30%. We undertook a retrospective chart review of 276 patients who were admitted to intensive care in a large university hospital. The period studied included patients from 23 February 2014 to 12 May 2021. Four groups were collected: COVID-19 Wave 1, COVID-19 Wave 2, influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…In this study, we used a combination of two or more microbiological markers for diagnosis. The incidence of CAPA in this prospective cohort of 160 patients was 18.75%, which is similar to that found in several studies [ 18 , 19 ]. By applying the 2020 ECMM/ISHAM consensus criteria however, the incidence in this study would have been 24.4% (n = 39).…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we used a combination of two or more microbiological markers for diagnosis. The incidence of CAPA in this prospective cohort of 160 patients was 18.75%, which is similar to that found in several studies [ 18 , 19 ]. By applying the 2020 ECMM/ISHAM consensus criteria however, the incidence in this study would have been 24.4% (n = 39).…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, empirical voriconazole was administered to cover a possible Aspergillus spp. co-infection, which was suspected due to the high dose dexamethasone treatment previously reported to increase the risk of infection with Aspergillus spp.in critically ill COVID-19 patients in the ICU patients ( 6 ). The following day his condition further deteriorated with increased need for oxygen therapy (10 L/min).…”
Section: Resultsmentioning
confidence: 99%
“… 17 Most studies exploring CAPA risk factors have either included all intubated patients or critically ill patients, hence excluding possibility of analysing this as a risk factor for CAPA. 18 , 19 …”
Section: Discussionmentioning
confidence: 99%
“…A recently published systematic review and meta‐analysis reported that based on sequential organ failure assessment score, CAPA patients had comparatively greater severity of illness at presentation 17 . Most studies exploring CAPA risk factors have either included all intubated patients or critically ill patients, hence excluding possibility of analysing this as a risk factor for CAPA 18,19 …”
Section: Discussionmentioning
confidence: 99%